Setting out a vision for the civil service in Ireland - Barrington, Anne; MacFeely, Steve; Carpenter, Breffini (2014)
For all the charges made against it, the civil service has worked with reasonable efficiency. It has served different Governments loyally and with regard to the national interest. In its long established traditions, it operates impartially. It has tried as best it could within the framework of its organisation and resources to promote the development of a nation; it has given its advice to Ministers fairly and honestly and, when given the final decisions of the Government, it has implemented them without reservation. The civil service has contributed much to what is progressive in our national life. - Reproduced.
Keywords: Civil service - Ireland; Civil service